Assessment of the Quality Attributes of Oat β-glucan Fortified Reduced-Fat Goat Milk Yogurt Supported by Microfluidization - Elif Ayse Anli; Asuman Gursel; Ayse Gursoy; Behic Mert (Foods, 2023)
In this study, goat milk blends (1.5% fat) fortified with 0%, 0.25%, and 0.50% oat β-glucan were coded as YC, Y1, and Y2 and MFYC, MFY1, and MFY2. Microfluidization was applied at 103.4 MPa pressure in a 100 µm-process chamber at one stage for MFYC, MFY1, and MFY2 prior to yogurt making. Phase separation occurred due to the casein-β-glucan interaction observed at the oat β-glucan ratio (≥0.25%) but was more distinct at 0.50%. Microfluidization solved the textural instability at all ratios of β-glucan; a creamy and less cohesive structure was maintained in all yogurt samples. Among the samples, Y2 and MFY2 were the least viscous (p < 0.05), and syneresis was the highest and the lowest for Y2 and MFY1, respectively (p < 0.01). Lightness (L*) decreased, and yellowness (b*) and greenness (a*) increased with oat β-glucan concentration (p < 0.01) and MFYC. MFY1 and MFY2 were brighter and less green (p < 0.05). Microfluidization enhanced sensory attributes and oat β-glucan suppressed the goaty and salty taste, but the cereal taste became more obvious with the increase in the oat β-glucan ratio. Y1 and MFY1 were generally acceptable, and Y2 was less (p < 0.01). A liquid-like structure was observed in Y2 and this affected the sensorial perception in Y2.